Immunohistochemistry of factor VIII, histology and morphometry in equine tendon treated with platelet- -rich plasma - Zandim, Bruna Mota; De Souza, Maria Verônica; Frassy, Luiza Neme; Vilória, Marlene Isabel Vargas; Maia, Leandro [UNESP]; Fonseca, Cláudio César; Valente, Fabrício Luciani; Do Carmo Lopes Moreira, José; Magalhães, Pablo Costa (My University, 2013)
The aim of this research was to verify the therapeutic effects of platelet-rich plasma (PRP) in the treatment of tendinopathy of the superficial digital flexor tendon as assessed by histological and morphometric evaluation, as well as to evaluate early changes in the expression of factor VIII by immunohistochemical analysis during the inflammatory and proliferative phases of healing process of PRP treated tendons compared to placebo. Five days after induction of tendinopathy by collagenase, the forelimbs of six horses were treated with intralesional PRP or 0.9% NaCl. Tendon biopsy was performed at 3 or 16 days after treatments. In both phases and with both treatments, the lesion area was filled with granulation tissue containing scattered collagen fibers with loss of parallelism, fibroblasts with varied morphology, neovascularization and hypertrophied endotenon. These characteristics were more evident during the proliferative phase and no differences were observed between treatments. A negative correlation between collagen fibers and moderately plump fibroblasts was observed. Immunohistochemistry staining was positive for factor VIII, without any differences between the treatments and tendon healing phases.
Imunoistoquímica do fator VIII, histologia e morfometria em tendão de equino tratado com plasma rico em plaquetas
Keywords: Growth factors; Horses; Platelet-rich components; Tendinous structures